2014
DOI: 10.3758/s13428-014-0490-y
|View full text |Cite
|
Sign up to set email alerts
|

The stochastically curtailed generalized likelihood ratio: A new termination criterion for variable-length computerized classification tests

Abstract: Computerized classification tests (CCTs) are used to classify examinees into categories in the context of professional certification testing. The term "variable-length" refers to CCTs that terminate (i.e., cease administering items to the examinee) when a classification can be made with a prespecified level of certainty. The sequential probability ratio test (SPRT) is a common criterion for terminating variable-length CCTs, but recent research has proposed more efficient methods. Specifically, the stochastical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
2
14
0
1
Order By: Relevance
“…In this study, Z 0.975 was 1.96 and Z 0.80 was 0.84. Therefore, the number of subjects in each group could be calculated as follows (15): Considering a dropout rate of broadly 10%, the number of subjects in each group was 26.97 (= 24.28/(1 2 0.10)), and a sample size of 54 (= 27 3 2) randomly assigned subjects was required. Based on our experience from previous clinical trials for treating diabetic foot ulcers, ;10% of subjects experienced unexpected events related to diabetesrelated complications and high-risk comorbidities.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In this study, Z 0.975 was 1.96 and Z 0.80 was 0.84. Therefore, the number of subjects in each group could be calculated as follows (15): Considering a dropout rate of broadly 10%, the number of subjects in each group was 26.97 (= 24.28/(1 2 0.10)), and a sample size of 54 (= 27 3 2) randomly assigned subjects was required. Based on our experience from previous clinical trials for treating diabetic foot ulcers, ;10% of subjects experienced unexpected events related to diabetesrelated complications and high-risk comorbidities.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Previous research (Finkelman, 2008(Finkelman, , 2010 had demonstrated the success of both methods when the TSPRT stopping rule is used. More recently, stochastic curtailment was also applied in conjunction with the GLR stopping rule and was shown to yield increased efficiency while maintaining similar accuracy (Huebner & Fina, 2014). However, as explained in the Introduction, no previous research had applied curtailment or stochastic curtailment to the CI stopping rule, which is preferable to the TSPRT and the GLR in some testing contexts.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The authors note that although Kullback-Leibler information has also been studied as an alternative to FI, the two item selection criteria perform very similarly in terms of efficiency and accuracy in practical testing situations (Lin, 2011). Moreover, recent studies on SCSPRT methodology (Finkelman, 2008(Finkelman, , 2010Huebner & Fina, 2015) use the FI index. Also, to mimic a practical testing situation, the Sympson-Hetter method of item exposure control (Sympson & Hetter, 1985) was used with a desired maximum exposure rate of 0.20.…”
Section: Simulation Studymentioning
confidence: 99%